2018
DOI: 10.1107/s1600577518001662
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Raman spectroscopy of lithium-ion battery electrolyte solutions in a flow cell

Abstract: The effects of varying LiPF salt concentration and the presence of lithium bis(oxalate)borate additive on the electronic structure of commonly used lithium-ion battery electrolyte solvents (ethylene carbonate-dimethyl carbonate and propylene carbonate) have been investigated. X-ray Raman scattering spectroscopy (a non-resonant inelastic X-ray scattering method) was utilized together with a closed-circle flow cell. Carbon and oxygen K-edges provide characteristic information on the electronic structure of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 53 publications
1
20
0
1
Order By: Relevance
“…The experimental conditions for each measured spectrum, in terms of applied temperature, pressure and resulting density are listed in SI-Table1. The XRS experiments were performed at beamline P01 of PETRA III using the XRS spectrometer 56 and at beamline ID20 of ESRF exploiting the large-solid-angle XRS spectrometer 57 . At beamline P01 spectra were measured with an overall energy resolution of 0.85 eV at a momentum transfer of (2.4 ± 0.3) Å −1 using an array of 12 spherically bend Si analyzer crystals at a fixed analyzer energy of 9.7 keV exploiting the Si(660) reflection in forward scattering.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental conditions for each measured spectrum, in terms of applied temperature, pressure and resulting density are listed in SI-Table1. The XRS experiments were performed at beamline P01 of PETRA III using the XRS spectrometer 56 and at beamline ID20 of ESRF exploiting the large-solid-angle XRS spectrometer 57 . At beamline P01 spectra were measured with an overall energy resolution of 0.85 eV at a momentum transfer of (2.4 ± 0.3) Å −1 using an array of 12 spherically bend Si analyzer crystals at a fixed analyzer energy of 9.7 keV exploiting the Si(660) reflection in forward scattering.…”
Section: Methodsmentioning
confidence: 99%
“…Raman spectroscopy can be also used in combination with hard X-rays as a bulk technique to analyse the electronic structure of electrode materials and electrolyte in LIBs, and due to the high penetration of hard X-rays, does not require high vacuum or any specific thin cell window. The detailed discussion of X-ray Raman spectroscopy (XRS) is out of the scope of this review, but fundamental examples can be found in [88,[91][92][93].…”
Section: Xrd Coupled With Other Techniquesmentioning
confidence: 99%
“…In this way, XRS combines the advantages of a hard X-ray probe (when compared with other spectroscopic methods) with the sensitivity of soft-XAS, enabling bulk studies under more challenging sample environments and in operando (Bergmann et al, 2002;Braun et al, 2015). So far, the XRS spectra of Li, C and O K-edges of different battery components (electrolyte solutions, anode and cathode materials) (Ketenoglu et al, 2018;Gog et al, 2009;Chan et al, 2011) have been investigated ex situ. Obtaining XRS data with a good signal-to-noise requires access to a wide angular range from the sample.…”
Section: X-ray Spectroscopymentioning
confidence: 99%